Biomarkers of Nutrition for Development (BOND): Vitamin B-12 Review - Allen, Lindsay H; Miller, Joshua W; de Groot, Lisette; Rosenberg, Irwin H; Smith, A David; Refsum, Helga; Raiten, Daniel J (The Journal of nutrition, 2018)
This report on vitamin B-12 (B12) is part of the Biomarkers of Nutrition for Development (BOND) Project, which provides state-of-the art information and advice on the selection, use, and interpretation of biomarkers of nutrient exposure, status, and function. As with the other 5 reports in this series, which focused on iodine, folate, zinc, iron, and vitamin A, this B12 report was developed with the assistance of an expert panel (BOND B12 EP) and other experts who provided information during a consultation. The experts reviewed the existing literature in depth in order to consolidate existing relevant information on the biology of B12, including known and possible effects of insufficiency, and available and potential biomarkers of status. Unlike the situation for the other 5 nutrients reviewed during the BOND project, there has been relatively little previous attention paid to B12 status and its biomarkers, so this report is a landmark in terms of the consolidation and interpretation of the available information on B12 nutrition. Historically, most focus has been on diagnosis and treatment of clinical symptoms of B12 deficiency, which result primarily from pernicious anemia or strict vegetarianism. More recently, we have become aware of the high prevalence of B12 insufficiency in populations consuming low amounts of animal-source foods, which can be detected with ≥1 serum biomarker but presents the new challenge of identifying functional consequences that may require public health interventions.